22-8m=-8m-11m

Simple and best practice solution for 22-8m=-8m-11m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 22-8m=-8m-11m equation:


Simplifying
22 + -8m = -8m + -11m

Combine like terms: -8m + -11m = -19m
22 + -8m = -19m

Solving
22 + -8m = -19m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '19m' to each side of the equation.
22 + -8m + 19m = -19m + 19m

Combine like terms: -8m + 19m = 11m
22 + 11m = -19m + 19m

Combine like terms: -19m + 19m = 0
22 + 11m = 0

Add '-22' to each side of the equation.
22 + -22 + 11m = 0 + -22

Combine like terms: 22 + -22 = 0
0 + 11m = 0 + -22
11m = 0 + -22

Combine like terms: 0 + -22 = -22
11m = -22

Divide each side by '11'.
m = -2

Simplifying
m = -2

See similar equations:

| 9+6m=45 | | -4-6n=5-9n | | (m^5n)^-2/m^-2n^3 | | x+3+3x-(6)=180 | | 1.2-0.3m=1.8 | | z(z^2+1)=5+z^3 | | 1=k+8/15 | | 6/7*9/16 | | -7k-k=-10k | | -116=-7x+2(-7x+5) | | 4.8/3 | | -7k-k=10k | | x(6x-6)=(6+8)(x-7) | | 15+3x+1=7x+1 | | 6(-2)-3(-5)/4-2 | | 3x^3+2x^2y+3xy^2+2y^3= | | 2a-5b/6a-4a+5b/4a+2 | | 3x^3+2x^2v+3xy^2+2y^3= | | 3x-4=6x+5 | | -7/8m=-2/3 | | 5.25x=15 | | 10n^2-5n-10=-6 | | 2/3x-5=x/4 | | 6^2-36/3^2*8-2 | | -15x+7x-1=3-8x | | 5.25+x=15 | | -x/-6=-2 | | 2y+(x+9)=98 | | 3/y+9/y=4 | | x+3/3+x+1/4 | | -4y^2-24y-30-x=0 | | 8+12a=4a+9a |

Equations solver categories